2023
DOI: 10.32598/jpcp.11.1.860.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Acceptance-and-Commitment-Based Parenting Training on Mood and Anxiety in Children and Self-compassion in Parents

Abstract: Objective: Depression and anxiety are common in children and a major cause of many illnesses and disabilities in this age group; Moreover, parents have the greatest impact on shaping the mental health and well-being of their children and there is a vast literature describing the importance of parenting factors in the development of depression and anxiety in children. Methods: We used the experimental research design in this study. The sample consisted of 34 children with depression and anxiety who were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…There have been no previous studies directly comparing the effectiveness of schema therapy and ACT on ambiguity tolerance, but the effectiveness of each intervention has been studied separately. Overall, the results are consistent with previous research (Arntz et al, 2022;Asli Azad et al, 2020;Azimifar et al, 2018;Baruch et al, 2009;Bratton et al, 2005;de Klerk et al, 2017;Farahzadi et al, 2018;Farrell et al, 2012;Farrell et al, 2009;Ghorbanikhah et al, 2023;Gillanders et al, 2015;Hasannezhad Reskati et al, 2020;McKay, 2012;Mogadam et al, 2018;Nikan et al, 2023;Nikrouy et al, 2022;Norozi et al, 2017;Öst, 2014;Ostadian Khani et al, 2021;Peeters et al, 2022;Renner et al, 2016;Rostami et al, 2019;Ruiz, 2010;Saffarinia & Azizi, 2019;Simpson et al, 2010;Younesi et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There have been no previous studies directly comparing the effectiveness of schema therapy and ACT on ambiguity tolerance, but the effectiveness of each intervention has been studied separately. Overall, the results are consistent with previous research (Arntz et al, 2022;Asli Azad et al, 2020;Azimifar et al, 2018;Baruch et al, 2009;Bratton et al, 2005;de Klerk et al, 2017;Farahzadi et al, 2018;Farrell et al, 2012;Farrell et al, 2009;Ghorbanikhah et al, 2023;Gillanders et al, 2015;Hasannezhad Reskati et al, 2020;McKay, 2012;Mogadam et al, 2018;Nikan et al, 2023;Nikrouy et al, 2022;Norozi et al, 2017;Öst, 2014;Ostadian Khani et al, 2021;Peeters et al, 2022;Renner et al, 2016;Rostami et al, 2019;Ruiz, 2010;Saffarinia & Azizi, 2019;Simpson et al, 2010;Younesi et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Various studies have confirmed the effectiveness of ACT in reducing depression symptoms (Ghorbanikhah et al, 2023;Öst, 2014), reducing anxiety symptoms (Öst, 2014;Ostadian Khani et al, 2021), improving quality of life and its dimensions, including physical health, psychological health, and social health (Öst, 2014;Rostami et al, 2019), enhancing psychological health and increasing hope for life (Mogadam et al, 2018;Nikrouy et al, 2022), reducing procrastination and improving academic performance (Golestanibakht et al, 2022;Jalili & Mahmoodi, 2021;Ofem, 2023), enhancing attachment quality and altruism in children with externalizing behavior problems (Azimifar et al, 2018;Ofem, 2023), reducing interpersonal problems and experiential avoidance (Baruch et al, 2009;Farahzadi et al, 2018;McKay, 2012;Norozi et al, 2017), and increasing self-compassion among self-harming students both in posttest and follow-up stages (Ghorbanikhah et al, 2023;Gillanders et al, 2015), and enhancing cognitive emotion regulation and increasing ambiguity tolerance in students with obsessive-compulsive disorder (Asli Azad et al, 2020).…”
Section: E-issn: 2981-2526mentioning
confidence: 96%
See 1 more Smart Citation